Gold-bearing veins around a felsic stock near Wawa, Ontario: implications for gold exploration - P. A. Studemeister (Canadian Institute of Mining, Metallurgy and Petroleum, 1985)
"A trondhjemite stock intrudes a volcanic sequence that has massive sulphide lenses and that is metamorphosed to the greenschist facies at Gutcher Lake, 25 km north of Wawa, Ontario. The stock is 4 km2 in plan and is partly enveloped by an aureole of chlorite-epidote-amphibolehornfels up to 1 km wide. Within this contact aureole, biotite is partly pseudomorphosed by chlorite;epidote and hornblende are mottled by chlorite, calcite, plus quartz; albite has 0% An to 8% An; and hornblende porphyroblasts have actinolite rims. The stock has chlorite pseudomorphous after biotite; and feldspar is mottled by white mica plus calcite and has a clear rim of albite. Fractures filled with quartz, calcite, ankerite, chlorite, white mica, pyrite, and native gold cross-cut the stock and its hornfels aureole. These gold-bearing veins are enveloped by foliated rocks with quartz, calcite, white mica, and chlorite that grade outward from the veins into trondhjemite or hornfels.The stock, emplaced into a submarine volcanic series, emanated heat that caused seawater to convect and formed a contact aureole of hornblende hornfels. The stock eventually intruded its aureole and this culminated with regional metamorphism to the greenschist facies. Regional metamorphism hydrated the stock and its hornfels aureole. Native gold precipitated with quartz along fractures from metamorphic flu ids in response to cooling and wallrock hydration. exploration for this type of gold deposits should focus around felsic intrusions that have albite and that have contact aureoles retrograded by regional metamorphism."